The VIPCALL Model for Empowering Pre-Service English Teachers in Islamic Primary School - Eko-Tanuso, Nur Antoni; Mujiyanto, Januarius; Hartono, Rudi; Pratama, Hendi (UIN Siber Syekh Nurjati Cirebon, 2025)
AbstractIslamic primary schools face a dual challenge, i.e. preserving religious pedagogical values while adapting to technology-enhanced learning. This study introduces a culturally based blended-learning model, VIPCALL: Visualization, Interactive, and Personalized Instruction through Collaborative and Assisted Language Learning, for teaching English at Madrasah Ibtidaiyah. The model was implemented during 17 Field Work Practice sessions from October to November 2024 and involved fourteen pre-service English teachers from seven Islamic elementary schools in West Java. Following a design-based research framework, data collection was made through observation, reflective journals, semi-structured interview sessions, students' questionnaires, and artifact analysis. Results indicate that VIPCALL significantly enhanced the creativity, digital literacy, and integration of Islamic values with interactive English learning of pre-service teachers. Students exhibited increased classroom engagement, improved mastery of vocabulary, and higher confidence to communicate in English. Quizizz, augmented-reality flashcards, activities based on Islamic stories, and games to learn vocabulary led to positive learning outcomes and proved adaptable to low-resource contexts. Overall, VIPCALL offers a scalable, culturally responsive pedagogical model grounded in the evidence that connects tradition and innovation, supports Sustainable Development Goal 4 (Quality Education), and offers practical guidance for teacher training and the use of technology in Islamic primary schools.Keywords: VIPCALL, blended learning, Madrasah Ibtidaiyah, pre-servis english teaacher, cultural responsive. AbstrakSekolah dasar Islam menghadapi tantangan ganda, yaitu melestarikan nilai-nilai pedagogis keagamaan sekaligus beradaptasi dengan pembelajaran yang didukung teknologi. Studi ini memperkenalkan model pembelajaran campuran berbasis budaya, VIPCALL—Visualization, Interactive, and Personalized Instruction through Collaborative and Assisted Language Learning—untuk pengajaran Bahasa Inggris di Madrasah Ibtidaiyah. Model ini diimplementasikan selama 17 sesi Praktik Kerja Lapangan (PPL) dari Oktober hingga November 2024 dan melibatkan empat belas calon guru Bahasa Inggris dari tujuh sekolah dasar Islam di Jawa Barat. Mengikuti kerangka penelitian berbasis desain, pengumpulan data dilakukan melalui observasi, jurnal reflektif, sesi wawancara semi-terstruktur, kuesioner siswa, dan analisis artefak. Hasil penelitian menunjukkan bahwa VIPCALL secara signifikan meningkatkan kreativitas, literasi digital, dan integrasi nilai-nilai Islam dengan pembelajaran Bahasa Inggris interaktif pada calon guru. Siswa menunjukkan peningkatan keterlibatan di kelas, peningkatan penguasaan kosakata, dan kepercayaan diri yang lebih tinggi untuk berkomunikasi dalam Bahasa Inggris. Quizizz, kartu flash augmented reality, aktivitas berbasis cerita Islami, dan permainan untuk mempelajari kosakata menghasilkan hasil pembelajaran yang positif dan terbukti dapat diadaptasi ke konteks dengan sumber daya terbatas. Secara keseluruhan, VIPCALL menawarkan model pedagogis yang terukur, responsif secara budaya, dan berlandaskan bukti yang menghubungkan tradisi dan inovasi, mendukung Tujuan Pembangunan Berkelanjutan 4 (Pendidikan Berkualitas), serta menawarkan panduan praktis untuk pelatihan guru dan penggunaan teknologi di pendidikan dasar Islam.Kata kunci: VIPCALL, blended learning, Madrasah Ibtidaiyah, calon guru bahasa Inggris, pedagogi responsif budaya.